+0  
 
0
70
1
avatar

14-[(-4)-(-6)]+(7-9)

Guest Sep 13, 2017
Sort: 

1+0 Answers

 #1
avatar+317 
0

First, let's solve whats in the brackets.

-4-(-6)

=-4+6

=2

 

Now let's do the other bracket.

7-9=-2

 

Finally, plug those two numbers into the expression.

14-2+(-2)

=14-2-2

=10

 

angel

ISmellGood  Sep 13, 2017

17 Online Users

avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details